Spectrum of bacterial keratitis at a tertiary eye center in Indonesia - Rifna Lutfiamida; Rien Widyasari; Kara Citra Kalandra (Microbiology Spectrum)
ABSTRACT The purpose of this study is to analyze the bacterial spectrum and antibiotic susceptibility patterns in bacterial keratitis at a tertiary eye center in Jakarta, Indonesia. The study design is a retrospective analytic study. A retrospective cross-sectional analytic review of medical records was conducted for patients with bacterial keratitis who underwent corneal cultures over an 8-year period. The study exclusively included eyes with culture-positive bacterial keratitis. The data were divided into two distinct periods: January 2012 to December 2017 and January 2018 to June 2020. A total of 129 eyes with keratitis were examined, and culture-positive bacteria were found in 74 eyes. Gram-negative bacteria were identified in 65 eyes (69.1%), and Gram-positive bacteria were identified in 29 eyes (30.9%). The most common bacteria identified was Pseudomonas aeruginosa (34 positive cultures, 36.2%). Gram-negative bacteria had the highest susceptibility toward ceftazidime (94.7%; 95% CI, 88.9–100). Gram-positive bacteria had the highest susceptibility toward vancomycin (100%; 95% CI, 98.8–100). Gentamicin demonstrated broad sensitivity across all bacterial types (85.7%; 95% CI, 78.2–93.2%), surpassing fluoroquinolones. There were no significant changes in antibiotic susceptibility patterns between the two periods studied (P > 0.05). The stability observed in both the bacterial spectrum and antibiotic susceptibility patterns throughout the study period indicates that the current empirical treatment is still effective. However, the results highlight gentamicin as a highly valuable option for the empirical treatment of bacterial keratitis, while targeted treatment with ceftazidime should be considered for Gram-negative infections and vancomycin for Gram-positive infections when culture results are available.IMPORTANCEBacterial keratitis poses a significant public health concern in Indonesia due to its potential for vision loss and morbidity. Understanding the spectrum of bacterial pathogens causing keratitis is crucial for guiding appropriate treatment strategies and improving patient outcomes. This study aims to investigate the prevalence, antibiotic susceptibility patterns, and risk factors associated with bacterial keratitis cases, providing valuable insights for clinicians to optimize management protocols and enhance the overall ocular health landscape in Indonesia or in other countries that have similar geographical conditions.